BENEFITS OF PHYSIOTHERAPY IN GAIT TRAINING IN PEOPLE AFFECTED WITH SPASTIC CEREBRAL PALSY (CIPEEX, 2022)
ABSTRACTCEREBRAL PALSY IS A SET OF MOVEMENT AND POSTURE DYSFUNCTIONS RESULTING FROM NON-PROGRESSIVE DISORDER THAT OCCURS IN THE DEVELOPMENT OF THE CENTRAL NERVOUS SYSTEM. CONNECTION, WHICH IS ALTERED, BETWEEN SENSORY AND MOTOR CORTICAL, IN CHILDREN WITH CEREBRAL PALSY CAN AFFECT MUSCLE FUNCTION, CAUSING INCOORDINATION OF MOVEMENT AND DIFFICULTY IN ACQUIRING AND IMPROVING VARIOUS MOTOR SKILLS. GAIT IN THESE CHILDREN DIRECTLY DEPENDS ON THE TYPE AND SEVERITY OF MOTOR IMPAIRMENT. ASYMMETRICAL GAIT IS THE RESULT OF VARIATIONS IN ITS PARAMETERS RELATED TO DELAY IN NEUROPSYCHOMOTOR DEVELOPMENT, MUSCULOSKELETAL DISORDERS AND/OR POSTURAL IMBALANCES. THE ARTICLE CONSISTS OF A REVIEW OF NARRATIVE LITERATURE. THE INCLUSION CRITERIA WERE DEFINED AS: MENTION TO GAIT TRAINING AND ITS FUNDAMENTALS IN MINORS WITH SPASTIC CEREBRAL PALSY BETWEEN THE AGE OF 2 TO 18 YEARS OLD, IN ADDITION TO BEING IN LANGUAGES ENGLISH AND PORTUGUESE AND ITS PUBLICATION DATE WAS BETWEEN 2017 TO 2022. EXCLUSION CRITERIA USED WERE: STUDIES THAT EXTRAPOLATE THE ESTABLISHED AGE GROUP, INCOMPLETE STUDIES. FOUND OUT 200 ARTICLES, AFTER WHICH 62 ARTICLES WERE EXCLUDED THAT DID NOT FIT THE INCLUSION CRITERIA BECAUSE THEY DID NOT ADDRESS THE THEME TREATMENT IN GAIT TRAINING AMONG OTHER TOPICS. THUS, 18 ARTICLES WERE INCLUDED IN THE REVIEW. INDEPENDENT GAIT IN CHILDREN WITH CEREBRAL PALSY HAS GREAT EFFECT ON DAILY QUALITY OF LIFE. THE MAIN GOAL OF REHABILITATION IN CHILDREN WITH CEREBRAL PALSY IS THE RECOVERY OF INDEPENDENT GAIT. HOWEVER, CHILDREN WITH CEREBRAL PALSY HAVE A RESTRICTED ABILITY TO MOVE THAT RESULTS IN GAIT DYSFUNCTION (SHORT PITCH, IDLING SPEED, SWING PHASE A VARIETY OF TECHNIQUES, ALLOWING TO REACH THE OBJECTIVES IMPOSED IN INTERVENTIONS, IN WHICH THEY ARE ADAPTABLE TO THE TYPES OF CEREBRAL PALSY AND THEIR LEVELS OF COARSE MOTOR FUNCTIONALITY, BEING THEN AN EFFECTIVE TREATMENT). THUS, IT IS IMPORTANT TO CHOOSE AN EFFECTIVE TRAINING METHOD TO IMPROVE THE BALANCE AND GAIT OF CHILDREN WITH CEREBRAL PALSY. GROSS MOTOR SKILLS CAN BE IMPROVED BY APPROACHES BASED ON MOTOR LEARNING. SUCH INTERVENTIONS HAVE BEEN IDENTIFIED IN PEDIATRIC REHABILITATION AS EFFECTIVE WAYS TO IMPROVE MOTOR CONTROL AND GROSS MOTOR SKILLS. THESE BEHAVIORS INVOLVE STRUCTURED FEEDBACK AND VARIABLE PRACTICE THAT FOCUS ON ACTIVITIES THAT HELP TO ACQUIRE AND RETAIN DAILY LIVING SKILLS. DAILY WALKING PERFORMANCE IS REPORTED TO BE POSITIVELY ASSOCIATED WITH PARTICIPATION IN MOBILITY-BASED LIFESTYLE HABITS. SPECIFICALLY, THE INABILITY TO ACHIEVE MODERATE TO HIGH STRIDE RATES IN CHILDREN APPEARS TO BE RELATED TO REDUCED PARTICIPATION IN DAILY ACTIVITIES. WALKING DURING ACTIVITIES OF DAILY LIVING INVOLVES THE USE OF JOINT COORDINATION AND THE PERFORMANCE OF COGNITIVE PROCESSES, SUCH AS MOVING THINGS, MANIPULATING TOOLS AND TALKING TO OTHER PEOPLE. THUS, A DUAL-TASK WORKOUT THAT COMBINES WALKING WHILE PERFORMING OTHER ACTIVITIES IS REQUIRED. IN CONCLUSION, GAIT TRAINING PRESENTS GOOD RESULTS, IN ADDITION TO DEMONSTRATING A VARIETY OF TECHNIQUES, ALLOWING TO REACH THE OBJECTIVES IMPOSED IN THE INTERVENTIONS, IN WHICH THEY ARE ADAPTABLE TO THE TYPES OF CEREBRAL PALSY AND THEIR LEVELS OF COARSE MOTOR FUNCTIONALITY, AND IS THEN AN EFFECTIVE TREATMENT.KEYWORDS: CEREBRAL PALSY; GAIT TRAINING; PHYSIOTHERAPY; SPASTIC.